Traditional Fermentation Process of Lais Fish (Cryptopterus Bicirrhis) in Butas Bagu Village, Sembakung District, Nunukan District, North Kalimantan - Siti Hajar; Novianti Novianti; Harianti Harianti (Publikasi Indonesia, 2024)
North Kalimantan (Kaltara), the 34th province in Indonesia, with its capital city in Tanjung Selor, has very abundant natural resources (SDA) potential. North Kalimantan has a coastline of 3,515 km, which holds a variety of capture fisheries potential. To find out the traditional fermentation process of Sikalut and Lais (Kryptopterus) fish in Butas Bagu Village. The purpose of this final project is to learn about the traditional fermentation process of lais fish (Cryptopterus Bicirrhis). Starting from Washing 1, Filleting, Disposing of Stomach Contents, Washing II, Draining Water, Salting, Freezing for 24 hours, Adding Cassava Dregs, and Putting Fish in Jars. Traditional fish processing should be done at night; the goal is to prevent flies from landing on the ingredients, and it should be done with caution if the preparations are mixed with other ingredients apart from cassava pulp or rice.